A prospective study of fecal calprotectin and lactoferrin as predictors of small bowel Crohn's disease in patients undergoing capsule endoscopy. (4th March 2017) - Bar-Gil Shitrit, Ariella; Koslowsky, Benjamin; Livovsky, Dan M.; Shitrit, David; Paz, Kalman; Adar, Tomer; Adler, Samuel N.; Goldin, Eran
Abstract: Background: Capsule endoscopy (CE) is often used to investigate small bowel Crohn's disease (CD). Aim : The aim of this study is to prospectively assess the value of fecal calprotectin and lactoferrin to predict CE findings. Patients and methods: Sixty-eight consecutive patients that were referred for CE were included. Stool samples for calprotectin and lactoferrin and blood samples were collected for relevant parameters. Correlation between fecal markers and CE findings was assessed and receiver operating characteristic (ROC) curves were built to determine the predictive values of fecal markers for the diagnosis of CD. Results: Fecal calprotectin data was available for all the patients and lactoferrin data for 38. CE findings compatible with CD were found in 23 (33%) patients and 45 (67%) were negative for CD. The average age of the CD group was 34 compared to 46 in the non-CD group ( p  = .048). Median calprotectin and lactoferrin in the CD group and in the control group were 169 mg/kg vs. 40 ( p  = .004) and 6.6 mg/kg vs. 1 ( p  = .051), respectively. The area under the ROC curve was 0.767 for calprotectin and 0.70 for lactoferrin. A fecal calprotectin concentration of 95 mg/kg and fecal lactoferrin of 1.05 mg/kg had a sensitivity, specificity, positive predictive value and negative predictive value of 77 and 73%, 60 and 65%, 50 and 50%, and 84 and 84% in predicting CE findings compatible with CD. Conclusions: Fecal markers are simple and noninvasive surrogates for predicting CE findings compatible with CD. Fecal markers can help determine which patients should be referred for CE. ClinicalTrials.gov Identifier: NCT01266629